2014
DOI: 10.1007/s40519-014-0136-1
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic characteristics of patients with bulimic symptomatology in an online post-treatment program: an exploratory study

Abstract: BackgroundNo former investigation has been performed related to the linguistic characteristics of patients with eating disorders using online synchronous communication mediums like chats.ObjectiveThe purpose of this study was to investigate the linguistic predictors of improvement in eating disorder-related attitudes, behaviours and emotional distress of patients with eating disorders.MethodsThirty-nine women, who had received treatment for bulimia nervosa or related eating disorders not otherwise specified, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The Hungarian versions of the DASS-21 (Mezei et al, 2015) and DCI (Martos et al, 2012) were administered. The PRQC (Fletcher, 2000) was translated from English to Hungarian following appropriate translation procedures.…”
Section: Methodsmentioning
confidence: 99%
“…The Hungarian versions of the DASS-21 (Mezei et al, 2015) and DCI (Martos et al, 2012) were administered. The PRQC (Fletcher, 2000) was translated from English to Hungarian following appropriate translation procedures.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 297 patients were included, of whom 130 were treatment as usual (TAU) patients. Overall, small short-term effects were found for the global of the Eating Disorder Examination Questionnaire (EDE-Q) [ 90 ] and EDI-2 total [ 63 , 65 ]. No effects were shown for binging, vomiting, and body mass index (BMI) [ 63 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…Fichter et al [ 63 ] found lower scores on the Structured Interview for Anorexic and Bulimic Syndromes (SIAB-EX [ 101 ]) “compensatory behavior” subscale and higher spontaneity to be predictive of successful relapse prevention. Mezei et al [ 65 ] identified a higher ratio of words related to family of origin, a higher BMI, and lower binging and emotional distress at baseline to be significantly associated with change in EDE-Q total. Furthermore, better compliance was associated with a better outcome also.…”
Section: Resultsmentioning
confidence: 99%